2020
DOI: 10.1016/j.ebiom.2020.102637
|View full text |Cite
|
Sign up to set email alerts
|

Canagliflozin impairs blood reperfusion of ischaemic lower limb partially by inhibiting the retention and paracrine function of bone marrow derived mesenchymal stem cells

Abstract: Background: Canagliflozin (CANA) administration increases the risk of lower limb amputation in the clinic. The present study aimed to investigate whether and how CANA interferes with the intracellular physiological processes of bone marrow derived mesenchymal stem cells (BM-MSCs) and its contribution to ischaemic lower limb. Methods: The in vivo blood flow recovery in ischaemic lower limbs following CANA treatment was evaluated. The cellular function of BM-MSCs after CANA treatment were also assessed in vitro.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Our previous study also showed that MIF rejuvenates aged human MSCs and improves myocardial repair [ 12 ]. MSCs achieve cardiac protective function mainly through paracrine factors such as exosomes [ 20 23 ]. Recent studies have shown that exosomes derived from MSCs reduce myocardial ischemic injury and preserve cardiac function after MI [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study also showed that MIF rejuvenates aged human MSCs and improves myocardial repair [ 12 ]. MSCs achieve cardiac protective function mainly through paracrine factors such as exosomes [ 20 23 ]. Recent studies have shown that exosomes derived from MSCs reduce myocardial ischemic injury and preserve cardiac function after MI [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…through paracrine factors such as exosomes. [20][21][22][23] Recent studies have shown that exosomes derived from MSCs reduce myocardial ischemic injury and preserve cardiac function after MI. 24,25 Compared with conventional stem cell transplantation therapy, exosome therapy showed no teratoma development, minimum immunogenicity, and little potential for tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown the protective effect of SGLT2 inhibitors (canagliflozin, empagliflozin, and dapagliflozin) against cardiovascular disease and death in patients with type 2 diabetes mellitus (Wiviott et al, 2019a;Arnott et al, 2020); however, oral admission of canagliflozin could increase the risk of limb amputation (Matthews et al, 2019), while both dapagliflozin and empagliflozin exhibit no evidence of risk (Dicembrini et al, 2019). Similarly, in vivo studies using diabetic HLI mice treated with orally administered canagliflozin results in a lower blood perfusion recovery compared to the control, while treatment with dapagliflozin results in a blood perfusion recovery comparable to that of the control (Lin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, while dapagliflozin is known as an oral anti-hyperglycemic drug, we found that blood glucose levels of diabetic HLI mice do not change significantly after intramuscular injection of dapagliflozin. On the other hand, Lin et al showed that, compared to that of the control group, oral administration of dapagliflozin does not improve blood perfusion recovery in diabetic HLI mice ( Lin et al., 2020 ). Although the detailed mechanisms involved need to be investigated further, these distinct effects are most plausibly due to the difference in administration method.…”
Section: Discussionmentioning
confidence: 99%